Visible spectro-photometric determination of cerberin in rat plasma - S. S. Prasanth, A. Rajasekaran (Journal of Applied Pharmaceutical Science, 2015)
The present paper aims to develop a simple direct colorimetric method for the determination of cerberin in rat plasma without any previous chemical separation of the cerberin from Cerbera odollam. The method is based on reaction of the cardenolide group of cerberin with 3,5-dinitro salicylic acid [DNS] in alkaline medium which yields a bright orange-yellow complex that exhibits absorption maxima at 370nm.Beer’s law obeyed in the concentration range of 50-250µg/mL. The result of the method was validated statistically and by recovery studies.
Keywords: Cerberin, Biological fluid, Visible Spectrometry.